2009
DOI: 10.12693/aphyspola.116.58
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Raman Studies οf MgO/SnO2Core-Shell Heteronanowires

Abstract: We have reported the fabrication of MgO core/SnO 2 shell nanowires, by a two-step evaporation process. Thermal annealing induced changes in morphology, in which the nanowire surface became rough by the agglomeration of SnO 2 shell layers and its crystallinity was enhanced. It was found that three fundamental modes (475, 634, 772 cm −1 ) and an infrared (IR)-active mode (682 cm −1 ) of rutile SnO 2 appeared in the Raman spectrum of MgO core/SnO 2 shell nanowires. By thermal annealing, the relative intensity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
5
9
0
Order By: Relevance
“…Raman peaks around 275.89, 442.15, and 1313.50 cm −1 (Figure 6(a)) are associated to the characteristics peaks of MgO and are found in good agreement with the previously reported research [46][47][48][49]. Generally, these bands are not present in the bulk MgO, so it confirms nanocrystalline phases within fabricated MgO [48] which is in concurrent to XRD analysis.…”
Section: Resultssupporting
confidence: 90%
“…Raman peaks around 275.89, 442.15, and 1313.50 cm −1 (Figure 6(a)) are associated to the characteristics peaks of MgO and are found in good agreement with the previously reported research [46][47][48][49]. Generally, these bands are not present in the bulk MgO, so it confirms nanocrystalline phases within fabricated MgO [48] which is in concurrent to XRD analysis.…”
Section: Resultssupporting
confidence: 90%
“…This suggestion allows assigning the band at 960 cm -1 as a LA+LO vibrational mode. The rather broad band composed of the line at 1080 cm -1 and accompanied by line at 1120 cm -1 was similar to those observed earlier [54,55] ascribed to the surface phonon modes in a TO-LO phonon gap [56]. Similarly to the authors of [56], we discovered, that TA phonon-and TO phonon-related Raman lines were not clearly observed, and the Raman lines of the TO-LO phonon gap were significantly suppressed in the most of our NPs.…”
Section: Raman Spectrasupporting
confidence: 87%
“…Moreover, Li and coworkers [ 20 ] reported the effect of uptake of synthetized nanoparticles such as rod-like hydroxyapatite into the hepatoma cells. Furthermore, in a very prestigious study, Cao and coworkers [ 21 ] reported the mechanism of inhibition of proliferation of hepatocellular carcinoma cells in unique in vitro and in vivo investigations.…”
Section: Introductionmentioning
confidence: 99%